'Surplus Profits' and Progressive Land Ownership: A Marxist Perspective. Issue 3 (2nd July 2016) - Potts, Nick
Abstract : Firstly I outline Shan Turnbull's idea of businessmen earning 'surplus profits' on their investments, like a shopping centre, and how potentially the use of progressive forms of land ownership may eliminate, or capture, these 'surplus profits' to the advantage of the local community. Next I explain Marx's view of how profit is produced and distributed in our capitalist economy. This allows us to see how Turnbull's 'surplus profits' are no better or worse ethically than profit in general under capitalism. I then focus on how Marx imagines the value of fixed capital is determined and how it can, or crucially cannot, return to the capitalist in money, a non-fixed form of value. Finally I return to the question of the potential usefulness of alternative progressive forms of land ownership to local communities, now guided by Marx's framework of how value and profit are produced and distributed in our capitalist society.